PERAN KEPALA SEKOLAH DALAM MEMBERDAYAKAN ALUMNI UNTUK MENINGKATKAN DAYA SAING SEKOLAH - Sandi, Abdi Ari Sandi; Ikhwan, Afiful; Syam, Aldo Redo (PGMI Department of Institut Agama Islam Ibrahimy Genteng Banyuwangi, Indonesia, 2025)
This study aims to examine the role of school principals in empowering alumni and its impact on the competitiveness of schools. Empowering alumni is considered an important strategy in enhancing the quality of education, school reputation, and career opportunities for students. Using a qualitative approach and case study method, this research involves several schools that have successfully empowered alumni. The main findings of this study indicate that school principals can leverage alumni in various programs such as mentoring, collaboration with industries, and contributions to the development of school facilities. This study also reveals that empowering alumni can improve the competitiveness of schools by strengthening the school's reputation and expanding career opportunities for students. The contribution of this research lies in integrating the school leadership theory and Michael E. Porter's competitive strategy in the context of alumni empowerment.